Antibacterial bisabolane sesquiterpenoids and isocoumarin derivatives from the endophytic fungus Phomopsis prunorum. (June 2020) - Qu, Hui-Rong; Yang, Wen-Wen; Zhang, Xue-Qing; Lu, Zhen-Hong; Deng, Zhang-Shuang; Guo, Zhi-Yong; Cao, Fei; Zou, Kun; Proksch, Peter
Graphical abstract: Highlights: Four new compounds were isolated from an endophytic fungus Phomopsis prunorum . Compounds (±)-1 were isolated as a racemic mixture with a ratio of 55: 45. The absolute configurations of (±)-1 were determined by ECD calculation. Compounds (+)-1 and 5 displayed moderate antibacterial activity. Abstract: A pair of new phenolic bisabolane-type sesquiterpenoid enantiomers (±)- phomoterpenes A and B [(±)-1 ] and two known analogues (2 and 3 ), together with two new isocoumarins, phomoisocoumarins C‒D (4 ‒5 ), were isolated from an endophytic fungus Phomopsis prunorum (F4-3). Their structures were elucidated by comprehensive spectroscopic analysis. The enantiomeric separation for (±)-1 were achieved by chiral-HPLC, and their absolute configurations were assigned by electronic circular dichroism (ECD) calculation. Compounds (+)-1 and 5 exhibited moderate antibacterial activity against plant pathogenic bacteria Pseudomonas syringae pv. Lachrymans with MIC values of 15.6 μ g/mL.